2016
DOI: 10.1039/c5sc03291a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient electrochemical reduction of CO2 to CH4 in an ionic liquid using a metal–organic framework cathode

Abstract: It has been discovered that Zn metal-organic framework (Zn-MOF) electrodes and ionic liquids are an excellent combination for the efficient and selective reduction of CO2 to CH4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
154
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(154 citation statements)
references
References 53 publications
0
154
0
Order By: Relevance
“…It should be noted that the outstanding catalytic activity of partially oxidized 4-atom-thick Co for CO 2 reduction and its synthetic strategy provide new opportunities to tailor the structure and oxidation degree of nanostructured metal catalysts. Among highvalence metal oxides and sulfides, MoO 2 [159] promising catalytic activity, especially in ionic liquid containing electrolytes. Except for metal and metal compounds, non-metal or littlemetal electrocatalysts have demonstrated unique properties for CO 2 reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the outstanding catalytic activity of partially oxidized 4-atom-thick Co for CO 2 reduction and its synthetic strategy provide new opportunities to tailor the structure and oxidation degree of nanostructured metal catalysts. Among highvalence metal oxides and sulfides, MoO 2 [159] promising catalytic activity, especially in ionic liquid containing electrolytes. Except for metal and metal compounds, non-metal or littlemetal electrocatalysts have demonstrated unique properties for CO 2 reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Kumar et al demonstrated a Cu 3 (BTC) 2 (BTC = 1,3,5-benzenetricarboxylic acid) MOF film as an efficient electrocatalyst for the selective reduction of carbon dioxide to oxalic acid in N,N-dimethylformamide containing tetrabutylammonium tetrafluoroborate [158]. Recently, Kang et al deposited Zn-BTC MOF on carbon paper as an electrocatalyst for CO 2 reduction with ionic liquids as the electrolytes [159]. The morphology of the Zn-MOF had a significant effect on performance, and the sheet-like Zn-MOF exhibited the highest activity due to its large electroactive surface areas.…”
Section: Covalent or Metal Organic Framework (Cofs Or Mofs)mentioning
confidence: 99%
“…reduction or charge driving. Thus, this system can be used in metallic oxidation, 23 reductive synthesis, 24 electrophoretic deposition, [62][63][64][65] and two-step synthesis. 66 When electrodes are used to generate metal ions, the anode and cathode electrodes always consist of the same metal.…”
Section: Methodsmentioning
confidence: 99%
“…Hupp and co-workers developed this idea to deposit electroactive MOF thin films on transparent conductive FTO electrodes using the electrophoretic deposition method. [63][64][65][66] These authors first synthesized four typical MOFs, such as NU-1000, UiO-66, HKUST-1 and MIL-53, which presented some defects resulting in partial negative charges on the MOF surfaces. Then, the MOF particles were deposited on the positively charged electrodes of two identical FTO substrates.…”
Section: Deposition Of Mof Thin Films On Glassmentioning
confidence: 99%
See 1 more Smart Citation